Information and communication technologies and China’s international communication to the world - Debao Xiang; Weihan Cai (Revista Teknokultura, 2023)
Over four decades, ICT rapidly proliferated in China, transforming, and reshaping the country’s international communication in theory and practice. In parallel with economic achievements after the reform and opening-up, China aspires to enhance accordingly its international influence, thus requiring its media to emerge on the global stage. The article suggests that ICT plays a significant role in driving Chinese media’s global outreach, thereby enhancing soft power and improving its national image. Against the backdrop of continuous hegemony and unbalance in the global communication networks, the Belt and Road Initiative (BRI) launched by China aims to benefit developing countries in the Global South by constructing ICT infrastructures. Following the practice, the concept of a Community of Shared Future for Mankind was advanced to promote multilateral cooperation and better communication. China shoulders unprecedented responsibilities in an increasingly multipolar world where a new global communication order is expected.